EXPERIMENTAL FORMULATION OF ANTI FOULING PAINT WITH TRIBUTYL TIN OXIDE ASTOXIC PIGMENT - PILLAI, A. G GOPALAKRISHNA; NAIR, N UNNIKRISHNA (Fishery Technology, 2016)
Results of the experimental formulation of ;J.n antifouling paimincorporating TBTO as toxic pigment are presented in this paper.Of the various resins tested, namely, phenolic, cashew nut shell liquid(CNSL), epoxy, li11seed oil with rosin and limed rosin, the paintcompositiOn with limed rosin gave the critical leaching rate of TBTOÂ·Acid alkali test showed dissolution of matrix and visible migrationof toxin to the surface. Accelerated corrosion tests had not recordedany signs of corrosion in panels painted with or without bariercoat. Raft exposure studies indicated that the new formulation couldresist fouling accumulation on painted panels for 9 months.